2008
DOI: 10.1002/pssb.200879599
|View full text |Cite
|
Sign up to set email alerts
|

Suspended and non‐suspended carbon nanotube transistors for NO2 sensing – A qualitative comparison

Abstract: A qualitative comparison of the NO2 sensitivity of carbon nanotube field effect transistors (CNFETs) has been performed on CNFETs with 1) suspended channels, and 2) channels that are in contact with the SiO2 substrate. No significant response difference to NO2 is apparent in the two CNFET configurations. Therefore, the SiO2 substrate acting as a dominant indirect sensing mechanism can be ruled out.Additionally, two measurement modes in CNFETs are presented and discussed. The measurement modes are: 1) chemiresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Concerning FETs devices, the substrate contributes to electronic doping and therefore to gate hysteresis and reduced performance . Chemical , optical or displacement sensors fabricated out of suspend‐ ed nanocarbons exhibit enhanced characteristics and electromechanical resonators can only be realised using this type of geometry. Combining the above with DEP will be a major step towards enhanced performance nanocarbon devices with a large scale integration density.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning FETs devices, the substrate contributes to electronic doping and therefore to gate hysteresis and reduced performance . Chemical , optical or displacement sensors fabricated out of suspend‐ ed nanocarbons exhibit enhanced characteristics and electromechanical resonators can only be realised using this type of geometry. Combining the above with DEP will be a major step towards enhanced performance nanocarbon devices with a large scale integration density.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the intense study on the mechanism that regulates CNT chemiresistors, there is still a lack of consensus on how NO x and NH 3 molecules interact with CNTs [23,24]. The main sensing mechanisms that have been identified are the alteration of the Schottky barriers at the interface between CNTs/metal electrodes [25][26][27], the adsorption of target gas molecules at the interstitial sites in the CNT bundles [28][29][30] and direct charge transfer from the gas molecules on the SWNTs [31]. While experimental results confirmed that both Schottky barrier modulation and charge transfer between adsorbate molecules and CNTs play a crucial role in the sensing 4 mechanism [26,28,32], the scenario is more complex when considering networks of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of semiconductors has been investigated in transistors for NO 2 detection. A range of sensing layers, such as amorphous organic semiconductors,21, 22 porous silicon,23 silicon nanowires,24 carbon nanotubes,25–33 and metal oxide nanowires,34 were used. In all cases changes in current upon NO 2 exposure has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%